2011
DOI: 10.1007/s00701-011-1241-9
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4 expression is not elevated in mild hydrocephalus

Abstract: Our results indicate that aqp-4 is not up-regulated during the initial stages of hydrocephalus. This implies that aqp-4 may not play a significant role in hydrocephalus compensation until severe ventricular dilatation occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Several descriptive expression studies in hy-drocephalus provide indirect evidence for a role of AQP4 in hydrocephalus. Though no change in brain AQP4 expression was reported in a rat model of mild hydrocephalus produced by kaolin injection [23] , other rat kaolin model studies reported greatly increased AQP4 expression [24] or complex time-and region-dependent alterations in AQP4 expression [25] . Increased AQP4 expression was found in congenital hydrocephalic Texas rats [9] , in dogs with idiopathic communicating internal hydrocephalus [26] , and in a rat model of inflammatory communicating hydrocephalus in which AQP4 expression correlated with the severity of hydrocephalus [27] .…”
Section: Aqp4 and Hydrocephalusmentioning
confidence: 99%
“…Several descriptive expression studies in hy-drocephalus provide indirect evidence for a role of AQP4 in hydrocephalus. Though no change in brain AQP4 expression was reported in a rat model of mild hydrocephalus produced by kaolin injection [23] , other rat kaolin model studies reported greatly increased AQP4 expression [24] or complex time-and region-dependent alterations in AQP4 expression [25] . Increased AQP4 expression was found in congenital hydrocephalic Texas rats [9] , in dogs with idiopathic communicating internal hydrocephalus [26] , and in a rat model of inflammatory communicating hydrocephalus in which AQP4 expression correlated with the severity of hydrocephalus [27] .…”
Section: Aqp4 and Hydrocephalusmentioning
confidence: 99%
“…AQP4 can facilitate water passing from ventricles into brain parenchyma and then to the systemic circulation [ 1 ]. Whether the disturbance in AQP4 is contributes to hydrocephalus or is protective remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrocephalus is a central nervous system disorder that is commonly due to an imbalance between cerebrospinal fluid production and absorption. Excessive accumulation of cerebrospinal fluid leads to ventriculomegaly, increased intracranial pressure, and impaired neuronal functions [ 1 ]. At present, shunting is the main therapeutic method for treating hydrocephalus, but it has a high failure rate.…”
Section: Introductionmentioning
confidence: 99%
“…Even though there are quite a lot of aquaporins (water channel proteins) expressed in the CNS, Aquaporin 4 (AQP4) is the major one in the brain, and is expressed in astroglial end feet around the surface of capillaries related to the BBB, glia limitans, and ependyma [ 93 , 94 ]. IS induces both immediate and delayed cell death, which is accompanied by a robust inflammatory response and cerebral edema that can exacerbate injury during reperfusion [ 94 , 95 ].…”
Section: Hmgb1 and Edema Formation In Ismentioning
confidence: 99%
“…Brain edema is the main cause of death in patients with large infarction. AQP4, a water channel protein, is predominantly located in astroglial end feet [ 93 , 94 ] and has been shown to play an important role in water transport in the brain [ 94 , 96 ]. Also, AQP4 is considered to contribute to brain edema, particularly as AQP4-deficient mice have improved outcome following focal ischemic injury [ 94 , 97 ].…”
Section: Hmgb1 and Edema Formation In Ismentioning
confidence: 99%